2023
DOI: 10.1136/openhrt-2023-002273
|View full text |Cite
|
Sign up to set email alerts
|

External validation and updating of prediction models of bleeding risk in patients with cancer receiving anticoagulants

Abstract: ObjectivePatients with cancer are at increased bleeding risk, and anticoagulants increase this risk even more. Yet, validated bleeding risk models for prediction of bleeding risk in patients with cancer are lacking. The aim of this study is to predict bleeding risk in anticoagulated patients with cancer.MethodsWe performed a study using the routine healthcare database of the Julius General Practitioners’ Network. Five bleeding risk models were selected for external validation. Patients with a new cancer episod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 24 publications
1
1
0
Order By: Relevance
“…In fact, genetic factors and disease severity were not available in SEER-Medicare data and dynamic features (i.e., cancer progression, new diagnosis of diseases) were not included in the models due to complexities. Similar to previous risk scores, we found that bleeding history was an important factor in prediction of subsequent major bleeding [ 17 , 55 ]. Second, we excluded patients who have already initiated OACs before AFib diagnosis and those who initiated AFib during follow-up because OACs may increase risk of bleeding.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…In fact, genetic factors and disease severity were not available in SEER-Medicare data and dynamic features (i.e., cancer progression, new diagnosis of diseases) were not included in the models due to complexities. Similar to previous risk scores, we found that bleeding history was an important factor in prediction of subsequent major bleeding [ 17 , 55 ]. Second, we excluded patients who have already initiated OACs before AFib diagnosis and those who initiated AFib during follow-up because OACs may increase risk of bleeding.…”
Section: Discussionsupporting
confidence: 85%
“…Such poor performance suggested complex interactions between patients’ characteristics and outcomes in the presence of cancer. First, although we obtained additional cancer characteristics compared with traditional risk scores, the performance was not improved [ 55 ]. This may suggest that our models failed to capture important features in prediction of major bleeding.…”
Section: Discussionmentioning
confidence: 99%